Oral Rehabilitation of a Severely Resorbed Edentulous Maxilla with Screwed-retained Hybrid Denture Using Cresco System: A Case Report - Turkyilmaz, Ilser; Patel, Neal S.; McGlumphy, Edwin A. (European Journal of Dentistry, 2008)
Due to the angulation of maxillary bone as the maxillary bone resorption occurs from a buccal to palatal direction, bucco-lingually tilted implant placement is more likely especially in the posterior maxilla. The aim of this paper was to present a case restored by using a maxillary hybrid denture using Cresco method. A 59-year-old woman with an edentulous maxilla and five missing mandibular teeth was referred for implant treatment. Six months after sinus lift operation, four mandibular implants and six maxillary implants were placed. Due to the bucco-lingual tilt of two implants, the Cresco method was chosen to fabricate the metal framework for the maxillary hybrid denture that was delivered four months after implant placement. The main advantages of the Cresco method are a perfectly passive framework fit and corrected screw access holes. All ten implants placed were considered successful at 1-year recall, and no screw access holes were seen in the buccal part of the maxillary acrylic teeth.It was concluded that such screw-retained maxillary hybrid denture using the Cresco method met the esthetic expectations of a highly demanding patient. (Eur J Dent 2008;2:220-223)
Keywords: Tilted implant; Hybrid; Maxilla; Early loading